Banking Hegemony over the State Civil Apparatus: Gramsci's Analysis of Decree-Based Credit Culture in the Perspective of Islamic Economics - Muhammad Taufik Rahman; Desi Erawati; Siswandi; Hendra (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Banking credit practices using the Decree of Appointment as collateral have become a systemic phenomenon among State Civil Servants in Indonesia. This study aims to analyze how the SK-based credit mechanism operates as an instrument of banking hegemony that normalizes debt in the lives of ASN and reviews this phenomenon through an Islamic economic perspective. Using a qualitative method with a literature study approach and critical analysis, this research dissects the power relations between banking institutions and ASN using Antonio Gramsci's theory of hegemony. The research findings indicate that banks, particularly Regional Development Banks, exercise hegemony through